Barrier height enhancement and temperature dependence of the electrical characteristics of Al Schottky contacts on p-GaAs with organic Rhodamine B interfacial layer - Soylu, Murat; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2012)
In this work, two types of Schottky barrier diodes (SBDs) with and without Rhodamine B interfacial layer, were fabricated and measured at room temperature in order to investigate the effects of the Rhodamine B interfacial layer on the main electrical parameters. It was seen that the barrier height (BH) value of 0.78 eV calculated for the Al/Rhodamine B/p-GaAs device was higher than the value of 0.63 eV of the conventional Al/p-GaAs Schottky diodes. It has been observed that the Rhodamine B film increases the effective BH by influencing the space charge region of GaAs. The main diode parameters such as the ideality factor (n) and zero-bias BH of SBD with Rhodamine B interfacial layer were found to be strongly temperature dependent and while the BH decreases, the ideality factor increases with decreasing temperature. It has been concluded that the temperature dependent characteristic parameters for Al/Rhodamine B/p-GaAs SBDs can be successfully explained on the basis of thermionic emission (TE) mechanism with Gaussian distribution of the barrier heights. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Inorganic semiconductor; Organic compound; Electrical parameters; Temperature effect